Comparison of APACHE II, SAPS II, SAPS II expanded and GCS scoring systems in an intensive care unit in Turkey - Karataş Koçberber, Emine; Kızılaslan, Deniz; Erdoğan, Cem; Apikoğlu Rabuş, Şule (Springer, 2020)
[Abstract Not Available]
Keywords: APACHE II; SAPS II; GCS Scoring Systems